Pengembangan Pembelajaran Sistem Operasi Bagi Mahasiswa Universitas Bina Darma - Rasmila Rasmila; Indra Jasa Suhastra; Eagle Devara; Muhammad Ilham Al Fasya; Dimas Bagas Putra; Dasril Kholid (Jurnal Publikasi Teknik Informatika, 2024)
The rapid progress of information technology (IT) has created major challenges in interpersonal relationships, whether between individuals, communities, countries, or even clans. The development of information and communication technology has led to the emergence of new ideas among the general public. This causes the need for people who have the ability and high motivation to participate in the development of technology and information. .The research method uses a questionnaire method. According to Sukardi (1985) a questionnaire is a set of questions or statements that must be answered by respondents. This development method consists of several stages - In this research, we succeeded in collecting questionnaire response data from Binadarma students regarding the development of operating system learning. Data analysis shows that the majority of respondents expressed a high level of understanding of operating system material in the group interactive assignment learning method with a percentage of 56%, where students were 30% and female students were 26% and in the method of using technology as part of the process of learning operating system material with a percentage of 56%. where students are 26% and female students are 30%. However, there are difficulties faced by some students using the lecture method in understanding the material with a percentage of 62%, where 34% of students and 28% of female students. And in the statement based on learning sources, the majority of Binadarma students showed a high level of understanding of the material in learning sources through creative and interesting operating system material with a percentage of 68%, where students were 36% and female students were 32%.